DESAIN MITIGASI RISIKO MENGGUNAKAN HOUSE OF RISK PADA PROSES RANTAI PASOK GARAM OLAHAN (Case Study: PT. Garam Unit Camplong): Risk Mitigation Design Using House of Risk in Processed Salt Supply Chain Process (Case Study: PT. Garam Unit Camplong) - Anang Siswanto; Johan Alfian Pradana; Saiful Rowi; Venus Khatta Salsabillah; Sindy N M Haristanti; Rudy Kurniawan; Evi Yuliawati; Khoirul Hidayat (Agroindustrial Technology Journal, 2022)
The supply chain cannot be separated from the activities of manufacturing and service activities. The very dynamic development proves that the emergence of various risks that have the opportunity to hinder the supply chain process itself. The design that will be achieved is risk mitigation using a house of risk in processed salt products. The procedures we use lead to the house of risk I and the house of risk II with the achievement of preventive action. The findings obtained are responses by mapping position repositioning based on background, training as a science development, work assignments according to detailed equipment analysis and recapitulation, replacement of parts that have the potential to hinder the production process and monitoring of estimated repair times in total productive maintenance. The importance of risk to supply chains requires better development and mitigation. This is the lowest level key to consistently achieving supply chain processes in accordance with the expectations of the users involved.